Keterlibatan Pengguna, Budaya Organisasi Dan Kompetensi Pengguna Terhadap Kualitas Sistem Informasi Akuntansi - Ari Ayu; Safria Syarifuddin (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of user involvement, organizational culture and user competence on the quality of accounting information systems. This research was conducted at PT Arista Jaya, South Sulawesi Province. The sampling technique used purposive sampling method with a total sample of 62 respondents from 95 total population. The main data collection is through the distribution of questionnaires with data analysis techniques using SmartPLS. The result is that all independent variables examined in this study have a positive and significant influence on the quality of the accounting information system. Findings on the user involvement variable are still lacking because the company only involves a few users in the design or development of the system used by the company so that the company must improve employee training and involve all users in system development. A positive culture in the organization must be maintained and maintained. User competence has a positive effect so that companies must continue to improve the competencies possessed by system users by participating in training. The findings of this study provide thoughts and input regarding the ability, organizational culture, and user competencies that are very important in improving the quality of a company's accounting information system.